2006
DOI: 10.1354/vp.43-4-552
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Myxoid Leiomyosarcoma with Widespread Metastases in a Cat

Abstract: Abstract. A 10-year-old domestic shorthair cat was spayed to remove bilateral ovarian masses and an enlarged uterus. Both ovaries were effaced by large, irregular, firm, glistening, white cystic masses filled with clear viscous fluid. The uterine lumen was filled with copious amounts of clear viscous fluid, and the uterus contained multiple, firm, glistening, white nodules. Histologic examination revealed an invasive spindle cell neoplasm with features of malignancy, and extensive hypocellular areas containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 9 publications
2
33
2
Order By: Relevance
“…However, even in cases with aggressive clinical course, microscopically no features of severe atypia may occur, and mitotic indeces can be low. In these cases, therefore, discrimination between malignant and nonmalignant forms is based on biological behavior (Cooper et al, 2006). Similarly, in the presented case only a few areas of mild nuclear atypia and low numbers of mitotic figures were observed.…”
Section: Results and Disscusionsupporting
confidence: 61%
See 3 more Smart Citations
“…However, even in cases with aggressive clinical course, microscopically no features of severe atypia may occur, and mitotic indeces can be low. In these cases, therefore, discrimination between malignant and nonmalignant forms is based on biological behavior (Cooper et al, 2006). Similarly, in the presented case only a few areas of mild nuclear atypia and low numbers of mitotic figures were observed.…”
Section: Results and Disscusionsupporting
confidence: 61%
“…Miller et al (2003) reported that leiomyomas, but not leiomyosarcomas were positive for estrogen receptor-alpha. However, in the case of feline myxoid leiomyosarcomas weak positive nuclear reactions in some neoplastic cells have been noted (Cooper et al, 2006). Although there is no data on the presence of progesterone receptors in myometrial tumors in cats, the strong positive nuclear reaction, noted in most tumor cells in this study, may suggest the tumor cells were well differentiated.…”
Section: Results and Disscusioncontrasting
confidence: 56%
See 2 more Smart Citations
“…(Miller et al 2003, Cooper et al 2006, Sapierzynski et al 2009. In this case the cat was displaying signs of prolonged and recurrent oestrus despite attempted ovariohysterectomy, and had abdominal distension, weight loss and pain.…”
Section: Discusssionmentioning
confidence: 84%